Status epilepticus and coma leading to death in a boy caused by Medium Chain Acyl CoA dehydrogenase deficiency - abasi, ezatollah; Ghazavi, Ahad; HassanvandAmouzadeh, Masoud; Valizadeh, Mohammad; AkhavanSepahi, Mohsen (Iranian Journal of Child Neurology, 2020)
MCADD(Medium-chain acyl-coenzyme A dehydrogenase deficiency) is an autosomal recessive disorder of fatty acid β-oxidation with prevalence of 1/1000 EU(Europian) countries and some more prevalence in the middle east and Arabian countries with close relative marriage and Iran included. MCADD is the most common inborn error of metabolism fatty acid β-oxidation in Caucasian gender.Herein we report a 7-year old boy presenting with afebrile serial seizures followed by loss of consciousness and death. The patient was diagnosed with MCADD by metabolic screening test using mass spectrometry.